“Ay de las épocas en que sus poetas / solo pueden escribir apocalipsis”: "Sílithus" (2020), a sea of futures - Martínez Fernández, Ángela (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article proposes an approach to Sílithus (2020), the work of Enrique Falcón published during the pandemic period. For this purpose, the study is divided around two axes: the contextual framework and the political proposal of the collection of poems. First, we understand Sílithus within the culture wars of the present time and, more specifically, within the wars that settle the (im)possible futures. Within a neoliberal context that blocks and kidnaps the political imagination and the capacity of subjects to produce emancipatory narratives, the poetry book emerges as a counter-narrative, as a counter-hegemonic narrative that seeks to open the way to other forms of social organization. From the establishment of the contextual framework, secondly, we enter fully into the textuality of Sílithus and the two worlds it imagines. The first, governed by the political authoritarianism of the "archons", violence, torture and the division of the territory is opposed to the second, led by the Elder Sisters and by the children of the days, whom they summon with their songs. After the climatic collapse, the children transform the principles that govern the social space and reclaim the power of the commons through the assemblies convened in the forests. Thus, we enter into the interior of a poetic and political gear that contains within it the formulation of a complex historical, social and cultural system.